The effect of fructose–induced metabolic syndrome on the histological structure and enteroendocrine cells in duodenum of rats - Yildiz, Mustafa; Kum, Sadiye (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Metabolic syndrome is a worldwide common disorder that coexists with abdominal obesity, high blood pressure, dyslipidemia, and high blood sugar. The purpose of this investigation was to examine the effects of metabolic syndrome on enteroendocrine cell count and histological structure in duodenum. The rats were separated into control and metabolic syndrome groups. Duodenum tissue sections were stained with hematoxylin–eosin for histomorphological examinations. Additionally, immunohistochemical analysis of duodenum showed the presence of somatostatin and gastrin immunoreactive cells. In duodenum, it was found that villus height, villus width, villus area and thickness of tunica muscularis significantly increased in metabolic syndrome group compared to control group. Similarly, it was observed that the numbers of somatostatin and gastrin immunoreactive cells in duodenum were significantly higher in metabolic syndrome group compared to control group. As a result, it was revealed that metabolic syndrome caused structural disorders in duodenum and changed enteroendocrine cell population. Thus, it can be assumed that intestinal functions may be negatively affected due to metabolic syndrome and digestive physiology may be disrupted.